Towards a Safer Internet of Things—A Survey of IoT Vulnerability Data Sources - Rytel, Marcin; Felkner, Anna; Janiszewski, Marek (Sensors (Basel, Switzerland), 2020)
The security of the Internet of Things (IoT) is an important yet often overlooked subject. Specifically, the publicly available information sources about vulnerabilities affecting the connected devices are unsatisfactory. Our research shows that, while the information is available on the Internet, there is no single service offering data focused on the IoT in existence. The national vulnerability databases contain some IoT related entries, but they lack mechanisms to distinguish them from the remaining vulnerabilities. Moreover, information about many vulnerabilities affecting the IoT world never reaches these databases but can still be found scattered over the Internet. This review summarizes our effort at identifying and evaluating publicly available sources of information about vulnerabilities, focusing on their usefulness in the scope of IoT. The results of our search show that there is not yet a single satisfactory source covering vulnerabilities affecting IoT devices and software available.